Readers, reading and libraries: Role games in the Casa de las Conchas Public Library (Salamanca) - Héctor Sevillano Pareja (FahrenHouse, 2012)
This article analyzes the profile of a prototype reader of role games books and the data were obtained through the collaboration of the responsible of the «Casa de las Conchas Public Library», located in Salamanca. For this study, we made a complete index, of existing data in the computer system, of users whose lent role game books, in the aforementioned library.